2020
DOI: 10.21203/rs.2.24391/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aucubin alleviates oxidative stress and inflammation via Nrf2-mediated signaling activity in experimental traumatic brain injury

Abstract: Background: Aucubin (Au) has anti-oxidative and anti-inflammatory bioactivities; however, its effects on a traumatic brain injury (TBI) model remain unknown. We explored the potential role of Au in a H 2 O 2 -induced oxidant damage in primary cortical neurons and weight-drop induced-TBI in a mouse model.Methods: Neuronal apoptosis, brain water content, histological damages and neurological deficits and cognitive functions were measured. We performed western blot, TdT-mediated dUTP Nick-End Labeling (TUNEL) sta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…has been widely used to treat many kinds of orthopaedic diseases in Asian countries for thousands of years. 23,24 The iridoid glycoside aucubin (C 15 H 22 O 9 ), the principle bioactive component of Eucommia ulmoides Oliv., has been reported to exert several pharmacological effects against inflammation, oxidation and bone loss. [23][24][25] In fact, aucubin has recently been shown to prevent apoptosis by regulating the level of autophagy in several disease models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…has been widely used to treat many kinds of orthopaedic diseases in Asian countries for thousands of years. 23,24 The iridoid glycoside aucubin (C 15 H 22 O 9 ), the principle bioactive component of Eucommia ulmoides Oliv., has been reported to exert several pharmacological effects against inflammation, oxidation and bone loss. [23][24][25] In fact, aucubin has recently been shown to prevent apoptosis by regulating the level of autophagy in several disease models.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 The iridoid glycoside aucubin (C 15 H 22 O 9 ), the principle bioactive component of Eucommia ulmoides Oliv., has been reported to exert several pharmacological effects against inflammation, oxidation and bone loss. [23][24][25] In fact, aucubin has recently been shown to prevent apoptosis by regulating the level of autophagy in several disease models. 26,27 However, little is known about whether and how aucubin might influence steroid-induced autophagy and apoptosis in osteoblast.…”
Section: Introductionmentioning
confidence: 99%
“…The primary compounds present in O. vulgaris are phenylethanol glycosides, iridoids, and flavonoids. Some compounds have been shown to have certain anti-inflammatory effects (Gong et al, 2020;Nigro et al, 2020;Wang et al, 2020d;Cicek et al, 2021;Tian et al, 2021). Through interviews with the local populace and hospital personnel in Inner Mongolia, we found that O. vulgaris is often used to treat RA; therefore, we conducted an in-depth study on the effects of O. vulgaris on RA.…”
Section: Introductionmentioning
confidence: 99%
“…18 Boosting Nrf2 antioxidant signaling provides remarkable neuroprotective effects against TBI-induced brain damage and neurological deficits. 19 –21 Therefore, Nrf2 is an interacting target for the treatment of TBI.…”
Section: Introductionmentioning
confidence: 99%